Ripley's Game - Cavani, Liliana; Ray Winstone; John Malkovich; Uwe Mansshardt; Hanns Zischler; Paolo Paoloni; Maurizio Lucà; Dougray Scott; Evelina Meghangi; Chiara Caselli; Lena Headey; Sam Blitz; et al. (Italy Baby Films, 2002)
Tom Ripley persuades a man to commit a murder for a large sum of money. The situation goes out of control, and that man must escape trouble.
Tom Ripley - cool, urbane, wealthy, and murderous - lives in a villa in the Veneto with Terry, his harpsichord-playing girlfriend. A former business associate from Berlin's underworld pays a call asking Ripley's help in killing a rival. Ripley - ever a student of human nature - initiates a game to turn a mild and innocent local picture framer into a hit man. The artisan, Jonathan Trevanny, who's dying of cancer, has a wife, young son, and little to leave them. If Ripley draws Jonathan into the game, can Ripley maintain control? Does it stop at one killing? What if Ripley develops a conscience? Terry prepares for her concert.
Older. Wiser. More talented.
Languages: English, Turkish Subtitle: Turkish
Keywords: Drama; Thriller